Uptake of recommended vaccines and its associated factors among Malaysian pilgrims - Goni, Mohammad Dauda (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2018)
The Muslims Holy pilgrimage tu Makkah and Madinah, Saudi Arabia is an annual event that records about 3 million pilgrims for Hajj and nearly 5 million pilgrims participating for the Minor Hajj known as Umrah conducted through the year (1, 2). Hajj pilgrims from more than 180 countries across the globe visit Saudi Arabia for the 2 pilgrimages yearly (3). These mass gatherings are characterized by many challenges like an increased risk of infection particularly the respiratory tract infections due to the enormous population density of the participants, shared accommodation, environmental pollution and extreme climatic conditions (-1, 5). Outbreaks of diseases like UniSZA/UHREC/2019/88) before this study. The data were treated with confidentiality and the results d id not identify the respondents personally.